Peningkatan Hasil Belajar Bahasa Indonesia Melalui Model Problem Based Learning Berbantuan Media Audio Visual - Mafaza, Sofia (Universitas Sebelas Maret, 2020)
The purpose of this research was to improve student learning outcomes in Bahasa Indonesia grade V elementary schools with a audio visual media assisted Problem Based Learning (PBL) learning model. The research conducted was a Classroom Action Research (PTK) with three cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle the students who completed after carrying out the post test were 70%. In the second cycle students who completed after carrying out the post test were 90%. In the third cycle students who completed after carrying out the post test were 100%. These results indicate that the Problem Based Learning (PBL) learning model can improve student learning outcomes, especially grade V Bahasa Indonesia at SD Negeri 01 Glandang academic year 2019/2020.